2017
DOI: 10.1038/s41598-017-14707-z
|View full text |Cite
|
Sign up to set email alerts
|

Cereal products derived from wheat, sorghum, rice and oats alter the infant gut microbiota in vitro

Abstract: The introduction of different nutrient and energy sources during weaning leads to significant changes in the infant gut microbiota. We used an in vitro infant digestive and gut microbiota model system to investigate the effect of four commercially available cereal products based on either wheat, sorghum, rice or oats, on the gut microbiota of six infants. Our results indicated cereal additions induced numerous changes in the gut microbiota composition. The relative abundance of bacterial families associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 95 publications
2
46
0
2
Order By: Relevance
“…Artificial gut models have therefore been used to discover the effect of nutritional supplements on infant gut microbiota (5), mechanisms by how commensals repress Salmonella virulence (6), and dose-dependencies between microbiota-targeting therapies and metabolite production (7). 55…”
Section: Introductionmentioning
confidence: 99%
“…Artificial gut models have therefore been used to discover the effect of nutritional supplements on infant gut microbiota (5), mechanisms by how commensals repress Salmonella virulence (6), and dose-dependencies between microbiota-targeting therapies and metabolite production (7). 55…”
Section: Introductionmentioning
confidence: 99%
“…As our fermentation experiments used previously frozen fecal samples, we verified that total SCFA production was strongly correlated between fresh samples and twice freeze-thawed samples (p < 0.0001, ρ = 0.75, Spearman correlation; Figure S4A). Since we elected to not provide our fermentation reactions with nutrients in excess of what was contained in the fecal slurries, we verified that there existed strong correlation in total SCFA production between PBS-grown and colonic medium-grown cultures (46), both when supplied with dextrin and inulin (Dextrin: p = 0.001, ρ = 0.68; inulin: p = 0.02, ρ = 0.51; Spearman correlations; Figure S5). We found that total SCFA production over control was positively correlated with the pH of starting fecal slurries (p = 0.003, ρ = 0.46; Spearman correlation; Figure S6A).…”
Section: Resultsmentioning
confidence: 93%
“…Once thawed, stool was weighed and placed into a polyethylene filter bag with 0.33mm pore size (Whirl-Pak B01385) and 10mL of anaerobic 1X PBS was added for each gram of stool, resulting in a 10% w/v fecal slurry, similar to previous studies (41, 42, 70, 71). During our validation experiments, a medium designed to simulate colonic contents was used in place of 1X PBS to create stool slurries (46). The filter bag was then closed and placed into a stomacher (Seward Stomacher 80) where the contents were homogenized on the medium speed setting for 60 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second set of demonstration experiments, we used the MicDrop platform to explore the dynamics of human gut microbiota in artificial gut systems. Such systems have been used when in vivo microbiota research is challenging, including measuring the effects of nutrition on the infant gut, systematic antibiotic testing, and investigating chemotherapy-induced dysbioses 47,48,49 . Still, a recurring challenge of artificial gut models has been their inability to completely reconstruct in vivo microbial communities.…”
Section: Resultsmentioning
confidence: 99%